A Control Strategy of DFIG under Unbalanced Grid Voltage - Xiao, Hui; Liu, Feiyan (Elektronika ir Elektrotechnika, 2013)
Under an unbalanced power grid voltage conditions, the DFIG’s stator side active power, reactive power, and electromagnetic torque will generate twice-multiplied frequency pulse quantities. In this paper, a double SRF (synchronous rotating coordinate system) control strategy was advanced. This strategy will produce a corresponding rotor voltage and current when controlling the DFIG’s rotor voltage and current, and then control them to eliminate the effects of an unbalanced grid voltage. The simulation model was set up using the software EMTP-RV, and the DFIG’s stator side active power, reactive power, and electromagnetic torque were analysed using both the DFIG conventional stator voltage oriented vector control strategy and the double SRF DFIG control strategy under unbalanced power grid voltage conditions. It is verified that the double SRF control strategy can effectively eliminated twice-multiplied frequency pulse quantity of the electromagnetic torque, reactive power and total mechanical power under unbalanced power grid voltage conditions. It has great significance to the DFIG stability working by using the double SRF control strategy in the DFIG control system. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.2426